2000
DOI: 10.1002/(sici)1096-8644(200005)112:1<49::aid-ajpa6>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Auricular exostoses in the prehistoric population of Gran Canaria

Abstract: Auditory exostoses are bone anomalies located in the external auditory canal. The bulk of clinical observations and some experimental data support the idea that their development depends on prolonged exposure to cold water. This study was performed in order to analyze the prevalence of auditory exostoses among the prehispanic population of Gran Canaria, comparing it between men and women and between individuals buried in coastal regions and central highlands. We analyzed 323 crania, 41 of which showed auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
14

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 21 publications
2
38
0
14
Order By: Relevance
“…Altas freqüências dessa anomalia foram registradas em pessoas envolvidas em atividades aquáticas intensas (Kroon et al, 2002), como surfistas, mergulhadores e pessoas responsáveis pela obtenção de recursos aquáticos (Standen et al, 1997). Apesar de causas genéticas já terem sido consideradas como determinantes da exostose auditiva, atualmente considera-se que sua etiologia esteja associada a fatores ambientais, especialmente ao contato dos canais auditivos com água fria (Van Gilse, 1983;Kennedy, 1986;Deleyiannis et al, 1996;Standen et al, 1997;Chaplin & Stuart, 1998;Velasco-Vazquez et al, 2000).…”
Section: Patologia óSseaunclassified
“…Altas freqüências dessa anomalia foram registradas em pessoas envolvidas em atividades aquáticas intensas (Kroon et al, 2002), como surfistas, mergulhadores e pessoas responsáveis pela obtenção de recursos aquáticos (Standen et al, 1997). Apesar de causas genéticas já terem sido consideradas como determinantes da exostose auditiva, atualmente considera-se que sua etiologia esteja associada a fatores ambientais, especialmente ao contato dos canais auditivos com água fria (Van Gilse, 1983;Kennedy, 1986;Deleyiannis et al, 1996;Standen et al, 1997;Chaplin & Stuart, 1998;Velasco-Vazquez et al, 2000).…”
Section: Patologia óSseaunclassified
“…In some studies no clear sexual differences are seen, at least at the statistical level of significance (e.g. Dutour and Onrubia-Pintado, 1991;Okumura et al, 2007;Velasco-Vazquez et al, 2000;Villotte et al, 2014), suggesting that both sexes were engaged in aquatic activities in these groups, while in other studies a significant difference is shown, usually with males having higher frequencies (e.g. Kennedy, 1986;Özbek, 2012;Standen et al, 1997).…”
Section: Potential Of Eae Linked To Aquatic Resource Exploitation By mentioning
confidence: 94%
“…Crowe et al, 2010;Cooper et al, 2010;Hurst et al, 2004;Ito and Ikeda, 1998;Özbek, 2012;Standen et al, 1997;Velasco-Vazquez et al, 2000;Villotte et al, 2014). The rate of interobserver error for qualitative methods can be quite high, however (5 to 15% according to Gregg and McGrew, 1970;Villotte et al, 2014, but see Crowe et al, 2010, likely due to lack of clear definition of the transition between grades.…”
Section: Recording Eaesmentioning
confidence: 99%
See 2 more Smart Citations